The right to write the city: Lefebvre and graffiti - Zieleniec, Andrzej (Environnement urbain)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2016)
Modern graffiti has become a universal urban phenomenon, an almost ubiquitous feature of towns and cities across the world. This paper will situate the practice and production of graffiti within various urban contexts (aesthetic, political, economic, social and semiotic) through the seminal works Henri Lefebvre as a means for analysing and understanding the complexity of the modern urban and to contextualize and explore graffiti’s role in challenging and contesting the socio-spatial norms of increasingly privatized and commodified public and social space. That is, to read graffiti as a means for reclaiming and remaking the city as a more humane and just, social space.